Analysis of lung function and survival in RECAP: An open-label extension study of pirfenidone in patients with idiopathic pulmonary fibrosis - Costabel, Ulrich; Albera, Carlo; Bradford, Williamson Z.; Hormel, Phil; King, Jr., Talmadge E.; Noble, Paul W.; Sahn, Steven A.; Valeyre, Dominique; du Bois, Roland M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: RECAP is an open-label extension study evaluating pirfenidone in patients with idiopathic pulmonary fibrosis (IPF) who completed the Phase 3 CAPACITY program. Objective: We examined the effect of pirfenidone on lung function and survival in patients who were previously randomised to the placebo group in one of the two CAPACITY studies and received pirfenidone for the first time in RECAP. Methods: Eligible patients received oral pirfenidone 2403 mg/day. Forced vital capacity (FVC) was measured at baseline and at weeks 12, 36, and 60. To facilitate comparison with CAPACITY outcomes, analyses were based on patients newly treated with pirfenidone in RECAP who had baseline FVC and carbon monoxide diffusing capacity (DLCO) values that met CAPACITY entry criteria. Results: A total of 178 patients were included in the analysis. Among these, 16.3% experienced an FVC decline ≥10% at week 60, compared with 16.8% and 24.8%, respectively, in the CAPACITY pirfenidone (n=345) and placebo (n=347) groups. The mean change from baseline to week 60 in %FVC was –5.9%, compared with –7.0% and –9.4% in the CAPACITY pirfenidone and placebo groups. Overall survival was similar to that of pirfenidone treated patients in CAPACITY. Treatment was safe and generally well tolerated; the type and frequency of adverse events were consistent with previous clinical experience. Conclusion: FVC and survival outcomes in IPF patients newly treated with pirfenidone in RECAP were similar to those in the CAPACITY pirfenidone group. These data provide further evidence to support the use of pirfenidone in patients with IPF.